Islamic Republic of Afghanistan : Enhanced Heavily Indebted Poor Countries Initiative; Decision Point Document and Debt Sustainability Analysis. (IMF Staff Country Reports; Country Report, 2007)
This paper presents the Islamic Republic of Afghanistan's decision point and debt sustainability analysis under the Enhanced Heavily Indebted Poor Countries Initiative. Protracted conflict and political instability have undermined Afghanistan's socioeconomic development, resulting in widespread poverty and weak social development. Nevertheless, Afghanistan's economy has achieved a major recovery since late 2001, with robust gross domestic product growth, albeit from a low level. The absence of officially recognized poverty estimates has prevented a systematic diagnosis of poverty in Afghanistan.